How Cinderella Came Late to the Ball: The Development of Radio Studies in the United Kingdom and Europe - Starkey, Guy (Media - Culture - Social Communication, 2019)
This paper examines the reasons for radio studies being relatively slow to develop as a field of academic study in the UK and in other contexts, mainly European. It contrasts the longevity of the medium, its hundred-year history, its durability in response to numerous challenges from other media and its relative cheapness to resource in educational contexts, with a far from impressive record in attracting the attention of academics and students in higher and further education. Tracing media education back to Frank Raymond Leavis and other influences, the paper invokes Reithian traditions to explain the absence of radio from a nascent subject so maligned in the second half of the twentieth century. It compares and contrasts the medium with others which have attracted far greater attention and argues that the tendency of media academics to ignore radio leaves a significant hole in the media studies curriculum. On a more positive note, the paper discusses the current state of radio studies in the UK and Europe, reconciling teaching and research with national and international networks and a number of initiatives intended to promote understanding and academic engagement with radio.